Continued treatment with secukinumab is associated with high retention or regain of response. (17th July 2019) - Augustin, M.; Thaci, D.; Eyerich, K.; Pinter, A.; Radtke, M.; Lauffer, F.; Mrowietz, U.; Gerdes, S.; Pariser, D.; Lebwohl, M.; Sieder, C.; Melzer, N.; et al.
Summary: Background: Conventional analyses present aggregate data, masking late responders and efficacy reductions. Secukinumab, a fully human monoclonal antibody that selectively neutralizes interleukin (IL)‐17A, shows sustained efficacy in moderate‐to‐severe psoriasis. Objectives: To determine stability of response to secukinumab, changes in efficacy were assessed in individual patients. Methods: This is a post hoc analysis of two phase III randomized controlled trials, FIXTURE (trial registration: NCT01358578) and CLEAR (trial registration: NCT02074982). Patients received secukinumab 300 mg (FIXTURE and CLEAR), etanercept 50 mg (FIXTURE) or ustekinumab 45 or 90 mg (CLEAR) over 52 weeks. Mutually exclusive response categories were defined: ≥ 90% improvement in the Psoriasis Area and Severity Index (PASI 90) ('excellent'), ≥ 75% improvement in PASI (PASI 75) and < PASI 90 ('good') and < PASI 75 ('insufficient'). Reductions in efficacy were defined as shifts from higher to lower response categories between two consecutive visits maintained for a third consecutive visit. Loss of efficacy was defined as a reduction of efficacy resulting in 'insufficient' response. All comparisons are descriptive. Results: At 52 weeks, in CLEAR, 90·2% (303/336) of patients on secukinumab achieved stable efficacy without loss and 77·7% (261/336) showed stable efficacy without any reduction of response [74·3% (252/339) and 59·9% (203/339) of patients for ustekinumab]. In FIXTURE, 83·5% (273/327) and 66·4% (217/327) of patients on secukinumab had stable efficacy without loss or reduction of response [58·3% (190/326) and 42·6% (139/326) for etanercept]. Response was regained by continuing secukinumab treatment in 50% (8/16) of patients in CLEAR and 26% (9/34) in FIXTURE. Similar patterns were observed for other response definitions. Conclusions: Efficacy with secukinumab was stable over 52 weeks of treatment in most patients. Continued treatment with secukinumab resulted in regain of efficacy in some patients. Persistent loss of response was uncommon. What's already known about this topic? Secukinumab, a fully human monoclonal antibody that selectively neutralizes interleukin (IL)‐17A, shows significant and sustained efficacy in the treatment of moderate‐to‐severe psoriasis. Secondary loss of response may be experienced by a minority of patients treated with secukinumab, as with other biologics, but the extent of this and the potential for regain of efficacy with continued treatment is not well understood. What does this study add? To determine stability of response to secukinumab and inform clinical practice, changes in efficacy were assessed at individual patient level using response categories. Efficacy with secukinumab was stable over 52 weeks of treatment in most patients, and continued treatment with secukinumab resulted in efficacy regain after loss in some patients. Persistent loss of response was uncommon. Patient factors such as body weight may affect the likelihood of loss of efficacy. Abstract : Plain language summary available online Respond to this article